Overexpression and characterization of strep-tagged thermostable organic solvent-stable lipase from Bacillus sp. strain 42 - Raja Abd. Rahman, Raja Noor Zaliha; Tengku Abdul Hamid, Tengku Haziyamin; Mohamed , Abdallah Eltaweel; Basri, Mahiran; Salleh, Abu Bakar (Elsevier, 2008)
In addition to stability at high temperatures, thermophilic enzymes also possess great resistance against proteolysis, detergents and chaotropic agents (Sellek and Chaudhuri, 1999). For this reasons, there was more attention to consider for their future use in organic solvent. Bacillus sp. strain 42 producing a solventstable thermostable lipase was isolated from Malaysian palm oil mill effluent. The 1.2 kb gene (AY 787835) code for lipase was amplified using consensus primers based on multiple sequence alignment with thermostable genes. The gene was cloned into pQE-30UA and pET51b expression vectors. An overexpression was achieved in heterologous system using pET51b vector with Escherichia coli host strain BL21(DE3)pLysS. The optimum expression was after 24 h incubation at 37 ◦C and lipase activity was at 80.0 U/ml culture (160.0 U/mg protein) after induction with 0.5mM IPTG. Under strong T7 promoter system, expression using pET51b/BL21(DE3)pLysS host-vector system is 11.5 fold higher compared to pQE-30UA/M15(pREP4) host-vector system which achieved at 17 U/ml culture (34 U/mg protein). The fusion lipase in pET51b contained Strep-tag II affinity tag that in one step of purification, the lipase was purified to homogeneity using Strep-tag II agarose column with 1.3-fold purification factor and 70% recovery. Sodium-dodecyl sulphate polyachrylamide gel electrophoresis (SDS-phage) analysis showed that the molecular weight of fusion lipasewas about 43 kDa. The purified lipasewasmost active at 70 ◦C and pH 8.0 and was stable in a broad pH range 7–10. The lipase showed high stability with half life of 315 min at 60 ◦C, for 125 min at 65 ◦C and 45 min at 70 ◦C. By 30 min incubation in 25% (v/v) solvents with shaking rate at 150 strokes per min, the solvent stability of the enzyme was different depending on solvents and temperatures. The lipase was more stable in polar organic solvent such as DMSO, DMF, acetone, methanol, heptanol and octanol. In thiswork, thermostable and organic solvent stable lipase gene from Bacillus sp. strain 42 was successfully identified and overexpressed into high expression vector pET51b using host BL21(DE3)pLysS, under the control of T7 expression mechanism. The fusion enzyme was successfully purifie to homogeneity using Strep-tag affinity tag, and characterized. Stability of enzyme in organic solvent with low partition coefficient value (log P) will enable its future industrial use, for instance in biodiesel production.